PENDAMPINGAN PENGENALAN SISTEM PEMBAYARAN QUICK RESPONSE INDONESIA STANDARD (QRIS) SEBAGAI INOVASI PEMBAYARAN CASHLESS UKM DI DESA SUMURJOMBLANGBOGO, KEC, BOJONG, KAB, PEKALONGAN - Wenti Ayu Sunarjo; Siti Nurhayati; Isnah Karimah (PT. Berkah Digital Teknologi, 2023)
In line with the development of advanced technology and information, it will help the growth of the digital economy and accelerate a country's financial inclusion. One form of implementation of information technology and digital economic growth is non-cash transaction payments. This QRIS can be used in payment applications that have been installed on a smartphone that is connected to an internet connection. The applications in question; e-wallet (from banking and non-banking issuers) which is used as a server-based payment instrument and has obtained permission from Bank Indonesia. With non-cash payments using a QR Code, it will make it easier for transactions to be carried out between sellers and buyers by scanning the code provided by the seller. Through this Community Service activity, namely the introduction of the Indonesian Standard Quick Response (QRIS) payment system as a payment innovation for SMEs in the village of Sumatra Jomblangbogo, Kec, Bojong, Kab, Pekalongan, it is felt that it is very relevant to the problems that occur in the scope of grocery stores in PkM locations. Through activities to introduce the QRIS system, partners will be able to answer problems, such as not fully understanding the payment system which is safe, easy and minimal risk, as well as other difficulties experienced by SMEs such as providing change or petty cash. Abstrak Sejalan dengan perkembangan teknologi dan informasi yang maju akan membantu pertumbuhan ekonomi digital dan percepatan inklusi keuangan suatu negara. Salah satu bentuk pengimplementasian antara teknologi –infomasi dengan pertumbuhan ekonomi digital adalah pembayaran transaksi secara non – tunai. Penggunaan QRIS ini dapat digunakan pada aplikasi – aplikasi pembayaran yang telah terinstall di smartphone yang telah terhubung dengan koneksi internet. Aplikasi – aplikasi yang dimaksud; e-wallet (dari penerbit perbankan maupun non perbankan) yang digunakan sebagai instrumen pembayaran berbasis server dan telah mendapatkan izin dari Bank Indonesia. Dengan adanya pembayaran nontunai menggunakan QR Code akan memudahkan transaksi yang akan dilakukan antara penjual dan pembeli dengan scan code yang telah disedikan oleh penjual. Melalui kegiatan Pengabdian kepada Masyarakat ini, yaitu pengenalan sistem pembayaran quick response indonesia standard (qris) sebagai inovasi pembayaran UKM di desa sumurjomblangbogo, kec, bojong, kab, pekalongan dirasa sangat relevan dengan permasalahan yang terjadi di lingkup toko kelontong yang ada di lokasi PkM. Melalui kegiatan pengenalan sistem qris akan dapat menjawab permasalahn mitra, seperti belum sepenuhnya mengenal sistem pembayaran yang aman, mudah, dan minim risko, maupun kesulitan lain yang dialami UKM seperti menyediakan uang kembalian atau petty cash.